Cervical muscle morphometry and composition demonstrate prognostic value in degenerative cervical myelopathy outcomes - Naghdi, Neda; Elliott, James M.; Weber, Michael H.; Fehlings, Michael G.; Fortin, Maryse (Frontiers in Neurology, 2023)
Objectives: To examine whether preoperative cervical muscle size, composition, and asymmetry from magnetic resonance imaging (MRI) can predict post-operative outcomes in patients with degenerative cervical myelopathy (DCM).Methods: A total of 171 patients with DCM were included. Relative total cross-sectional area (RCSA), functional CSA (fat free area, FCSA), ratio of FCSA/CSA (fatty infiltration) and asymmetry of the multifidus (MF) and semispinalis cervicis (SCer) together (MF+SCer), and cervical muscle as a group (MF, SCer, semispinalis capitis, splenius capitis) were obtained from T2-weighted axial MR images at mid-disc, at the level of maximum cord compression and the level below. Univariate and multivariate linear regression analyses were used to assess the relationship between baseline cervical muscle measurements of interest with modified Japanese Orthopedic Association (mJOA), Nurick Classification, Neck Disability Index (NDI) and SF-36 health survey at 6-months and 12-months post-surgery.Results: Lower RCSA of MF+SCer, less CSA MF+SCer asymmetry and greater FCSA/CSA for the cervical muscle group (e.g., less fatty infiltration) and younger age were significant predictors of higher mJOA scores (e.g., less disability) at 6-months and 12-months post-surgery (all p<0.05). Greater CSA asymmetry in MF+SCer and lower FCSA/CSA (e.g., more fatty infiltration) for the cervical muscle group were significant predictors of higher Nurick scores (e.g., more disability) at 6-months and 12-months post-surgery (all p<0.05). Lower FCSA MF+Scer asymmetry, Lower FCSA/CSA asymmetry of muscle group and greater RCSA MF+SCer were significant predictors of higher NDI scores at 6-months and 12-months post-surgery. Finally, greater FCSA/CSA asymmetry of the MF+SCer and greater FCSA asymmetry of muscle group, greater RCSA of muscle group and greater CSA asymmetry of MF+SCer were significant predictor of lower post-operative SF-36 scores at 6 and 12-months post-surgery. This is a provisional file, not the final typeset article Conclusion: Our result suggested that cervical paraspinal muscle morphology, specifically greater asymmetry, and fatty infiltration may be important predictors of functional recovery and post-surgical outcomes in patients with DCM.